Pengaruh Pemberian Susu Kedelai Terhadap Kadar Glukosa Darah Pada Penderita Diabetes Melitus Type 2 di Puskesmas Pagar Jati Kecamatan Lubuk Pakam - Diana, Cut; Erna Elfrida Naiborhu; Nurmasyitah; Betty Nurmala Samosir; Karmila Br Kaban (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background: Diseases with a significant number of sufferers include cardiovascular disease, as well as cancer, hypertension and diabetes mellitus or commonly called degenerative diseases (Potter & Perry, 2018). The group of metabolic diseases that have abnormalities in insulin secretion, insulin action which has a characteristic KGD that exceeds normal limits (hyperglycemia) can be called diabetes mellitus. This disease can be experienced in children or adults. It can even exist without having signs of disease and can be known if a routine health check is carried out (Soegondo, 2017). Objective: To obtain results on the effect of giving soy milk on KGD in patients with type 2 diabetes mellitus in the working area of Pagar Jati Public Health Center, Lubuk Pakam District. Research design: Pre-experiment and purposive sampling technique with a sample of 50 respondens. Conclusion: KGD in patients with type 2 diabetes mellitus before being given soy milk was mostly in the range of 160 mg/dl – 200 mg/dl, KGD in patients with type 2 diabetes mellitus after being given soy milk was mostly <160 mg/dl, and found an effect on milk administration. soybeans on KGD in patients with type 2 diabetes mellitus. Keywords: Diabetes mellitus soy milk, blood glucose levels, KGD